Water Risk and Mining Firms’ Stock Return - Maryam Davallou; Shirin Mehrali (تحقیقات مالی, 2024)
ObjectiveAccess to sustainable water resources has recently been raised as a major challenge facing water-dependent companies. The mining industry is one of the huge water users, which can be severely affected by water crises. The purpose of the current research is to test the pricing of water risk in mining companies of the Tehran Stock Exchange (TSE) and to estimate the drop in the value of their shares in the event of a water crisis. MethodsConsidering that the availability of water resources hinges on rainfall levels in the catchment area, we assessed water risk using the Standard Precipitation Index (SPI). Employing seasonal data from 2007 to 2011, it used a dynamic panel regression model to assess the effect of water risk on stock returns, controlling for factors such as profitability, leverage, firm size, and capital intensity among 11 companies. Then, the probable loss in a water crisis scenario was calculated using the stress test in the framework of value at risk. Also, the effect of drought hazard index, firm size, and covariance of market return with SPI on the value at risk of firms were investigated. ResultsThe significance of the water risk effect on stock returns of mining companies indicates the pricing and the confirmation power of this risk factor to explain the changes in stock returns over time, in a way that one unit increase in water risk will cause a decrease of about 3% in the excess return of the firm’s stock three quarters later. Also, the results showed that the amount of rainfall and drought in the region affects the firm's stock returns only up to three seasons, and its long-term effect is zero with a slight tolerance. Additional research findings indicate that during water crises, mining companies may experience a decline in value ranging from 15 to 45 percent. However, there was no direct relationship between the drought risk index and the value at risk of the firm’s value. Further investigations confirmed the existence of a strong relationship between the value at risk and the correlation coefficient of SPI and the market return. This means that the more positive the correlation between SPI and market returns, the greater the value at risk of the firm in water crisis conditions. ConclusionWater risk can explain part of the changes in stock returns of mining companies. Although companies may be situated in similar drought-prone regions, the level of value at risk for their stocks varies i.e., in case of any water resource crisis, other factors affect water risk other than drought. The shareholders of the larger company will suffer relatively fewer losses due to water risk.